Interim results of a prospective, randomized, open-label, Phase 3 study of the long-term safety and efficacy of lasmiditan for acute treatment of migraine (the GLADIATOR study). (October 2019) - Brandes, Jan Lewis; Klise, Suzanne; Krege, John H; Case, Michael; Khanna, Rashna; Vasudeva, Raghavendra; Raskin, Joel; Pearlman, Eric M; Kudrow, David
Objectives: To address the need for long-term lasmiditan data, the GLADIATOR study evaluated the safety (primary) and efficacy (secondary) of lasmiditan for the intermittent, acute treatment of migraine attacks for up to 1 year. Methods: In this prospective, randomized, open-label, Phase 3 study, patients who had completed either of two single-attack studies were offered the opportunity to be randomized 1:1 to lasmiditan 100 mg or 200 mg. Patients were asked to use lasmiditan as the first treatment for each new migraine attack of at least moderate severity. Assessments occurred at baseline and at prespecified time increments up to 48 hours after each dose of study drug using an electronic diary, and safety was assessed throughout the study. Migraine Disability Assessment (MIDAS) was assessed at each visit. Results: As of the cut-off date for this interim analysis (6 March 2018), 1978 patients had received ≥ 1 lasmiditan dose and treated 19, 058 migraine attacks. Overall, treatment-emergent adverse events (TEAEs) were similar to those in the single-attack studies and included dizziness (18.6%), somnolence (8.5%), and paresthesia (6.8%). The frequency of TEAEs generally decreased with subsequent attacks. No treatment-related serious adverse events and no cardiovascular TEAEs potentially due to vasoconstriction were observed. For both lasmiditan doses, efficacy measures were generally consistent over study quarters and treated attacks. Overall, across all treated attacks at 2 hours post-dose, pain freedom was observed in 26.9% of the attacks treated with lasmiditan 100 mg and 32.4% of the attacks treated with lasmiditan 200 mg. MIDAS total scores decreased over time. Conclusions: The interim results of this long-term study showed intermittent lasmiditan (100 mg and 200 mg) to be generally well tolerated and efficacious for the acute treatment of migraine over a 1-year period. Trial registration number: NCT02565186;https://clinicaltrials.gov/ct2/show/NCT02565186